Synthesis and Biological Evaluation of Indole-2-Carboxamides with Potent Apoptotic Antiproliferative Activity as EGFR/CDK2 Dual Inhibitors - Lamya H. Al-Wahaibi; Yaser A. Mostafa; Mostafa H. Abdelrahman; Ali H. El-Bahrawy; Laurent Trembleau; Bahaa G. M. Youssif (MDPI AG, 2022)
The apoptotic antiproliferative actions of our previously reported CB1 allosteric modulators 5-chlorobenzofuran-2-carboxamide derivatives VIIa-j prompted us to develop and synthesise a novel series of indole-2-carboxamide derivatives 5a-k, 6a-c, and 7. Different spectroscopic methods of analysis were used to validate the novel compounds. Using the MTT assay method, the novel compounds were examined for antiproliferative activity against four distinct cancer cell lines. Compounds 5a-k, 6a-c, and 7 demonstrated greater antiproliferative activity against the breast cancer cell line (MCF-7) than other tested cancer cell lines, and 5a-k (which contain the phenethyl moiety in their backbone structure) demonstrated greater potency than 6a-c and 7, indicating the importance of the phenethyl moiety for antiproliferative action. Compared to reference doxorubicin (GI50 = 1.10 µM), compounds 5d, 5e, 5h, 5i, 5j, and 5k were the most effective of the synthesised derivatives, with GI50 ranging from 0.95 µM to 1.50 µM. Compounds 5d, 5e, 5h, 5i, 5j, and 5k were tested for their inhibitory impact on EGFR and CDK2, and the results indicated that the compounds tested had strong antiproliferative activity and are effective at suppressing both CDK2 and EGFR. Moreover, the studied compounds induced apoptosis with high potency, as evidenced by their effects on apoptotic markers such as Caspases 3, 8, 9, Cytochrome C, Bax, Bcl2, and p53.